Analisis SWOT Dalam Implementasi Digital Marketing Pada UMKM Warung Agrin - Asrikamongga, Aliva Erhan Sefira; Wahono, Budi; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The objectives of this study are: 1) To find out the implementation of digital marketing at Warung Agrin MSMEs, 2) To find out the SWOT analysis of digital marketing at Warung Agrin MSMEs, 3) To find out the digital marketing strategy at Warung Agrin MSMEs. This research uses qualitative research methods and uses data collection techniques through observation, interviews, and documentation with key, main, and supporting sources. Based on SWOT analysis with the process of identifying internal and external factors, the results of the position of strengths (strenghts) are greater than weaknesses. The total score of strengths (strenghts) is 2.40 while weaknesses (weaknesses) is 1.09. Then on the company's external factors, the position of opportunities is greater than threats. The total score of opportunities is 1.80 while the total score of threats is 0.93. On the SWOT diagram, the total IFAS score of 3.49 and EFAS score of 2.73 occupy quadrant 1 which supports an aggressive strategy. Aggressive strategies support companies to continue to maximize their strengths and opportunities to move forward and achieve greater success. The implementation of aggressive strategies in digital marketing at Warung Agrin includes the use of ads or advertisements and cooperation with influencers. This strategy allows Warung Agrin MSMEs to provide continuous information to the audience, and reach the wider community of consumers. Keywords: SWOT Analysis, Digital Marketing, MSMEs.